Expression of CD44 and its variants on gastric epithelial cells of patients with Helicobacter pylori colonisation - KELLEHER, DERMOT P (BMJ, 1996)
BACKGROUND--Studies have suggested that expression of the adhesion molecule CD44 may be of prognostic importance in gastric cancer. In addition, there is strong evidence that Helicobacter pylori has a role in gastric cancer. AIMS--To determine the expression of CD44 and its variants (v6, v9) and HLA class II molecules on human gastric epithelial cell and intraepithelial lymphocytes in patients with and without H pylori infection. PATIENTS--Eighteen patients (seven men and 11 women) attending for endoscopic evaluation because of upper gastrointestinal symptoms were included. An additional 10 patients (five men and five women) were analysed for CD44 variant expression). METHODS--Biopsy specimens were taken from the gastric antrum during endoscopy. Gastric epithelial cells and intraepithelial lymphocytes were examined by two colour flow cytometry and compared in patients with and without H pylori infection. RESULTS--Expression of CD44 and its variants (CD44 v9) was increased in epithelial cells but not in intraepithelial lymphocytes. Both epithelial cells and intraepithelial lymphocytes expressed higher levels of HLA class II molecules (DR and DP), possibly as a result of local cytokine production. Furthermore, results showed upregulation of CD44 on a gastric epithelial cell line (AGS) by cytokines and peripheral blood mononuclear cell supernatant. CONCLUSIONS--These data suggest that H pylori, either directly or through a local inflammatory response, is responsible for increased expression of CD44 and its variant CD44 v9. These data are of potential importance in relation to increased expression of CD44 and CD44 v9 on gastric carcinoma.
PUBLISHED
Keywords: Clinical Medicine